Guarigione di un cieco (Mc 8,22-26) nel contesto del Vangelo di Marco - Bąk, Tomasz Bartłomiej (The Biblical Annals, 2018)
The Gospel according to Mark strives after providing the answer to two fundamental questions who Jesus is and who his disciple should be. Thus, the Evangelist makes some attempts to depict the identity of Jesus emphasizing his being the Son of God (cfr. Mk 1:1; 15:39). What is more, setting the description of the road leading to Jerusalem in the centre of his literary work, the author of the gospel highlights the identity of the Jesus’ disciple, who is not always able to understand the one, who called him. The aim of this article is to present the way how the pericope about the cure of a blind man (Mk 8:22-26) is depicted in the dynamism of the whole gospel and how it corresponds with effort being made with the aim of answering the questions: who Jesus is and who his disciples should be. The text, which is written in accordance with the principles of synchronic analysis, is comprised of such sections: I Introductory issues (distinguishing of the pericope as the whole; textual criticism; defining of the internal structure; synoptic comparison); II. Exegetical analysis; III. The significance of the pericope in the context of the whole Gospel; In the analysis of the cure of a blind man (Mk 8:22-26) the disciples are presented as those who seem to remain “outside” Christ mystery. The pericope corresponds perfectly with the fact that they possess eyes that do not see (cfr. Mk 8:18) and they do not yet understand (cfr. Mk 8:21). Not only does Jesus open the eyes of the blind man but also wants to open the eyes of his disciples. Two stages of healing reveal that regaining sight fully is preceded by the period of “shortsightedness” when the disciple has a vision but still blurred. He follows Jesus to Jerusalem, though, he does not understand who Jesus is. The moment when he completely opens his eyes and understands becomes possible in the context of the Paschal Mystery.